2003
DOI: 10.1038/sj.jp.7210883
|View full text |Cite
|
Sign up to set email alerts
|

Closed Suctioning of Intubated Neonates Maintains Better Physiologic Stability: A Randomized Trial

Abstract: OBJECTIVE:To evaluate the physiological variance in a closed (CS) vs an open suction (OS) protocol in intubated infants. STUDY DESIGN:Infants were stratified into three weight groups in a randomized crossover trial. Heart rate, respiratory rate, blood pressure, oxygen saturation, transcutaneous oxygen and carbon dioxide, and end-tidal carbon dioxide were recorded prior to suctioning, during suctioning, and recovery to baseline. Following the procedures, recovery time to baseline parameters was measured. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 13 publications
(13 reference statements)
3
34
1
2
Order By: Relevance
“…A study of 200 neonates who weighed Ͻ 1,000 g found twice the recovery time with open suctioning versus closed suctioning. 57 In a smaller pediatric study the results were the same, indicating benefits from closed suctioning. In neonates receiving high-frequency oscillatory ventilation (HFOV), closed versus open suctioning produced essentially equal drops in saturation and heart rate, but recovery time from those drops was significantly longer in the open-suctioning group.…”
Section: Open Versus Closed Suctioningsupporting
confidence: 62%
“…A study of 200 neonates who weighed Ͻ 1,000 g found twice the recovery time with open suctioning versus closed suctioning. 57 In a smaller pediatric study the results were the same, indicating benefits from closed suctioning. In neonates receiving high-frequency oscillatory ventilation (HFOV), closed versus open suctioning produced essentially equal drops in saturation and heart rate, but recovery time from those drops was significantly longer in the open-suctioning group.…”
Section: Open Versus Closed Suctioningsupporting
confidence: 62%
“…1,19,32 Without prolonged and continuous cerebral and physiological monitoring (at least until disturbed variables return to baseline) during clinically indicated procedures, the duration of effects of tracheal suctioning on the cerebral circulation of ventilated premature infants was previously unknown. Additionally, while closed system tracheal suctioning, 8,9 pre-sedation with phenobarbital, 5,7 preoxygenation, 4 briefly increasing peak inspiratory pressure, and/or using pressure-regulated volume control ventilation may be superior in mitigating physiological disturbances, 9 we studied the effects of the method that we clinically used at the time.…”
Section: Discussionmentioning
confidence: 99%
“…This necessary procedure, however, is associated with a number of transient disturbances of systemic hemodynamics and gas exchange that may be associated with impaired cerebral blood flow (CBF) regulation and development of subsequent neonatal brain injury. Elevated blood pressure (BP), [1][2][3][4][5][6][7][8] bradycardia, 2-4,9,10 hypoxemia and arterial desaturation, [1][2][3][4][5][9][10][11] and hypercapnia, 11 as well as increased intracranial pressure 1,3,6,7,12 have been observed during and briefly after tracheal suctioning. Abrupt increases in BP may cause cerebral hyperperfusion and intraventricular hemorrhage (IVH) in infants with or without intact cerebral autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have compared the two methods, and there is little evidence to support the use of one over the other (6 -8). Both techniques have been shown to result in greater physiologic stability in neonates (9,10), and less loss of lung volume in adults (7,11) and children (12) than open suction, although large volume losses have been recorded with both closed and open methods (7,12,13). In the only neonatal study to date comparing lung volume changes, there was no difference in volume loss between open and closed suction during either conventional or high-frequency oscillatory ventilation (HFOV), and wide variation in losses with both methods (14).…”
Section: E Ndotracheal Tube (Ett) Suction Is Performed Periodicallymentioning
confidence: 99%